Dynamics of Prochlorococcus and Synechococcus at Station ALOHA Revealed through Flow Cytometry and High-Resolution Vertical Sampling - van den Engh, Ger J.; Doggett, Joseph K.; Thompson, Anne W.; Doblin, Martina A.; Gimpel, Carla N. G.; Karl, David M. (Frontiers in Marine Science, 2017)
The fluorescence and scattering properties of Prochlorococcus and Synechococcus at Station ALOHA as measured by flow cytometry (FCM phenotype) vary with depth and over a variety of time scales. The variance in phenotype may reflect genetic selection or physiological acclimation to local conditions. Observations before, during, and after a storm with deep water mixing show a short-term homogenization of the FCM phenotypes with depth, followed by a return to the stable pattern over the time span of a few days. These dynamics indicate that, within the upper mixed-layer, the FCM phenotype distribution represents acclimation to ambient light. The populations in the pycnocline (around 100 m and below), remain stable and invariant with light conditions. In samples where both cyanobacteria coexist, fluorescence properties of Prochlorococcus and Synechococcus are tightly correlated providing further evidence that FCM phenotype variability is caused by a common environmental factor(s). Measurements of the dynamics of FCM signatures provide insights in phytoplankton physiology and adaptation. More importantly, an FCM phenotype census of a water mass provides information about its origin and illumination history.